Interactions between ship rats and house mice at Pureora Forest Park. Issue 3 (3rd July 2018) - Bridgman, Lucy; Innes, John; Gillies, Craig; Fitzgerald, Neil; Rohan, Maheswaran; King, Carolyn
ABSTRACT: When the abundance of ship rats ( Rattus rattus ) is reduced, sympatric house mice ( Mus musculus ) are released from constraints of food shortage, intimidation or predation. As a result, mice may become either more abundant or more active and detectable. To distinguish between these effects, we monitored mice at eight sites within Pureora Forest Park during periods of rat removal and non-removal, and supplemented food in mouse-specific feeders to half of the sites. We used live-trapping to estimate mouse relative abundance, and tracking tunnels to detect activity. Mouse relative abundance increased when rats were removed, which correlated with increased mouse activity in tracking tunnels. Analysis of mouse capture probability showed that although rat population levels predominantly influenced mouse relative abundance, mouse detectability was also affected at a subtler level. Fluctuations in mouse relative abundance were driven by immigration, and there was evidence that mice were food-limited in the presence of abundant rats. However, this effect was not offset by supplementing food, so it is unlikely that exploitation competition alone limits mice in the presence of rats. Instead, when ship rats were abundant the danger to mice was likely to have limited their foraging opportunities. Evidence of direct predation of mice by ship rats was observed, but it is unclear what role direct predation plays in determining mouse abundance relative to risk effects.